Antibacterial Activity Test of Leaf Ethl Acetate Extract Distance of Fence (Jatropha curcasL.) Against Bacteria Propionibacterium Acnes and Staphylococcus Aureus - Ginting, Indra; Asriwati, Asriwati; Mayang, Mayang; Tambunan, Noviyanti (International Journal Papier Advance and Scientific Review, 2023)
Skin diseases are very easy to found in countries with a tropical climate. The climate that facilitate the development of bacteria, parasites, and fungi. Acne is a skin disease that occurs due to inflammation of the follicles polisebasea characterized by the presence of comedones, papules, pustules and nodules. Propionibacterium acnes and Staphylococcus aureus is a bacterium that play a role in the pathogenesis of acne that will cause inflammation. The study was to determine the concentration of ethyl acetate extract of leaves of jatropha effectively inhibits the growth of bacteria Propionibacterium acnes and Staphylococcus aureus. This study was experimental research that includes plant identification, manufacture of crude dru, ethyl acetate extract of jatropha, examination of the phytochemical screening, and test the antibacterial activity of extracts of jatropha leaves by the method of pitting using MHA media, the manufacture of the extract with maceration using solvent ethyl acetate. The results of phytochemical screening of Jatropha showed the presence of flavonoid compounds, alkaloids, saponins and tannins. The results of the antibacterial activity test showed that each concentration had an inhibitory response that was categorized as moderate to strong on Propionibacterium acnes bacteria with clear zone diameters of 10% (7.50mm), 20% (9.18mm), 30% (12.10mm), and 40% (15.16mm) in Staphylococcus aureus bacteria with a clear zone diameter of 10% (8.13mm), 20% (10.21mm), 30% (12.13mm), and 40% (15.53mm). The conclusion showed that the ethyl acetate extract of Jatropha leaves (Jatropha curcas L.) has antibacterial activity against Propionibacterium acnes and Staphylococcus aureus.